Clinical comparison of four hair removal lasers and light sources - Amin, Snehal P.; Goldberg, David J. (Journal of cosmetic and laser therapy, 2006)
Background and objective: There are few clinical studies directly comparing the efficacy of multiple hair removal systems in the same individual. This study evaluates the efficacy of four highly popular systems for laser hair removal. Methods: In this prospective comparison study, 10 subjects underwent treatment of unwanted hair on the back or thigh. Subjects were skin types I-III, aged 18-55 years. All were treated twice with (1) an intense pulsed light with a red filter; (2) an intense pulsed light with a yellow filter; (3) an 810 nm diode laser; and (4) a 755 nm alexandrite laser. Four treatment areas, using commonly accepted parameters for permanent hair reduction, as well as a control non-treated area were selected. Each treatment area was evaluated with a camera system specifically designed for hair counts at 1, 3, and 6 months after the second treatment by a blinded non-treating physician. Clinical results and adverse events were also noted. Results: Evaluation of photographs at 1, 3, and 6 months revealed a significant decrease in hair counts (∼50%) and hair coverage (∼55%). In the hairs that remained after two treatments, no statistical difference was noted in hair length or diameter. There was no statistical difference in efficacy between the four different light devices. Minimal transient adverse effects were noted from all systems. The cryogen spray-based alexandrite laser showed the highest pain scores. Conclusion: Although hair removal with commonly used systems is, as expected, highly effective, treatment with light-based devices can cause less pain, yet show efficacy similar to laser systems.